A Bioengineered Three-Dimensional Cell Culture Platform Integrated with Microfluidics To Address Antimicrobial Resistance in Tuberculosis - Magdalena K. Bielecka (American Society for Microbiology, 2017)
ABSTRACT Antimicrobial resistance presents one of the most significant threats to human health, with the emergence of totally drug-resistant organisms. We have combined bioengineering, genetically modified bacteria, longitudinal readouts, and fluidics to develop a transformative platform to address the drug development bottleneck, utilizing Mycobacterium tuberculosis as the model organism. We generated microspheres incorporating virulent reporter bacilli, primary human cells, and an extracellular matrix by using bioelectrospray methodology. Granulomas form within the three-dimensional matrix, and mycobacterial stress genes are upregulated. Pyrazinamide, a vital first-line antibiotic for treating human tuberculosis, kills M. tuberculosis in a three-dimensional culture but not in a standard two-dimensional culture or Middlebrook 7H9 broth, demonstrating that antibiotic sensitivity within microspheres reflects conditions in patients. We then performed pharmacokinetic modeling by combining the microsphere system with a microfluidic plate and demonstrated that we can model the effect of dynamic antibiotic concentrations on mycobacterial killing. The microsphere system is highly tractable, permitting variation of cell content, the extracellular matrix, sphere size, the infectious dose, and the surrounding medium with the potential to address a wide array of human infections and the threat of antimicrobial resistance. IMPORTANCE Antimicrobial resistance is a major global threat, and an emerging concept is that infection should be studied in the context of host immune cells. Tuberculosis is a chronic infection that kills over a million people every year and is becoming progressively more resistant to antibiotics. Recent major studies of shorter treatment or new vaccination approaches have not been successful, demonstrating that transformative technologies are required to control tuberculosis. We have developed an entirely new system to study the infection of host cells in a three-dimensional matrix by using bioengineering. We showed that antibiotics that work in patients are effective in this microsphere system but not in standard infection systems. We then combined microspheres with microfluidics to model drug concentration changes in patients and demonstrate the effect of increasing antibiotic concentrations on bacterial survival. This system can be widely applied to address the threat of antimicrobial resistance and develop new treatments.